2003
DOI: 10.1144/gsl.sp.2003.216.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence on the role of gas in sediment liquefaction and mud volcanism

Abstract: Mud volcanoes are structures that are formed through 'cold volcanism' and indicate soil liquefaction. Their evolution depends on the structure, state and excitation of fine-grained feeding sediments. The disturbance of the framework of a loose, fine-grained, saturated sediment causes shear deformation leading to a pore fluid pressure increase. Effective stresses are thereby reduced and can vanish; the soil is then totally liquefied. Small amounts of enclosed gas bubbles render the soil compressible and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The existence of intrusive mud chambers at intermediate to shallow depths (<2-4 km) is supported by observations of modern and fossil mud volcanoes as well as by geochemical analyses of erupted fluids (Deville et al, 2003;Planke et al, 2003;Mazzini et al, 2009). Physical modeling suggests the importance of gas in overpressured fluids to promote the liquefaction and fluidization of sediments to form mud chambers, which drive surface activity through a combination of overpressure and buoyancy (Pralle et al, 2003).…”
Section: Shallow Mud Chambersmentioning
confidence: 86%
See 1 more Smart Citation
“…The existence of intrusive mud chambers at intermediate to shallow depths (<2-4 km) is supported by observations of modern and fossil mud volcanoes as well as by geochemical analyses of erupted fluids (Deville et al, 2003;Planke et al, 2003;Mazzini et al, 2009). Physical modeling suggests the importance of gas in overpressured fluids to promote the liquefaction and fluidization of sediments to form mud chambers, which drive surface activity through a combination of overpressure and buoyancy (Pralle et al, 2003).…”
Section: Shallow Mud Chambersmentioning
confidence: 86%
“…Episodic extrusive activity is also favoured by the dynamics of mud chambers, which are driven in part by internal factors (pressures, buoyancy), as well as by tectonically-driven fluid fluxes (e.g. Deville et al, 2003;Pralle et al, 2003).…”
Section: Episodic Mud Extrusionmentioning
confidence: 99%
“…Bubbles may also drive other rheological changes. Pralle et al (2003), for example, found that injecting gas bubbles into a suspension of quartz powder promotes liquefaction.…”
Section: Bubblesmentioning
confidence: 99%
“…In industry, hydraulic fracturing is done to enhance oil and gas recovery [5][6][7], CO 2 sequestration [8], water well and geothermal energy production [9][10][11]. Related natural processes, such as subsurface sediment mobilization, are studied in earth sciences, where sand injectites, mud diapirs, and mud volcanoes are formed due to pore-fluid overpressure [12][13][14][15][16][17]. For example, the Lusi mud volcano in Indonesia is the biggest and most damaging mud volcano in the world [18], having displaced 40 000 people from their homes, and has been active since May 2006.…”
Section: Introductionmentioning
confidence: 99%